« first day (965 days earlier)      last day (4353 days later) » 

23:00
@caveman Can't you do some integration swapping using some theorems?
how does that help
No, no that.
0
Q: Proving $3n^3-11n+48 | n+3$

pourjourI'm really stuck while I'm trying to prove this statement: $\forall n \in$ $\mathbb{N}$ $3n^3-11n+48 | n+3$. I couldn't even how to start.

23:08
@pourjour What's the meaning of the |?
@GustavoBandeira it means $3n^3-11n+48 divise n+3$
@mixedmath, not at all pleased with your comment on my answer
What's the meaning of $\stackrel{?}{=}$ in $P\stackrel{?}{=}NP$?
@pourjour Divided by n+3?
@GustavoBandeira the opposite
@pourjour ?
23:12
@GustavoBandeira n+3 divised by 3n^3-11n+48
it seems weird
ok so could someone please show how to prove that
@pourjour, dont you know long division
@caveman I mean n+3 divised by 3n^3..............
@pourjour, you have ti backwards
d|n means there exists k with dk = n
@caveman yeah
I know what it means and I know what I've written
@pourjour, then why can you see that it's obviously false?
23:17
@caveman contre example
@pourjour, 48 doesn't divide 3 for example
ugh
sorry
I'm really stupid
@pourjour, yuo can accept my answer?
I couldn't notice that because I tough it's obvious
I really dislike mixedmaths comment on my answer
he was here and ignored me when I told him that
thanks
23:21
@caveman u deserve it
:D
@mixedmath, it's called long division - most learn in school.. Maybe we can let the OP decide for himself what helps him. — caveman 1 min ago
$\rm (ac,db) \color{#C00}{\stackrel{(1)}{=}} (ac,\color{#0A0}{(d,ac)}\color{blue}{(b,ac)})$ can you explain to me this
@pourjour, its just using (X,YZ) = (X,(X,Y)(X,Z))
which is deduced from (X,YZ) = (X,(X,YZ)) and (X,Y)(X,Z)|(X,YZ)
@caveman but this line mean Y=(X,Y) and Z=(X,Z)
23:32
can u please translate it to $(A|B)$
I'm not familiar with GCD
did you see my answer to your question?
1
A: number theory $\gcd(a,bc)=\gcd(a,c)$

cavemanDefinition The gcd $g = (x,y)$ is the universal $g$ satisfying $g|x$ and $g|y$. Universal here means that if $g'$ satisfies $g'|x$ and $g'|y$ then $g'|g$. Note that universals are unique. Theorem $(a,b)=1$ implies $(a,bc) = (a,c)$. We need to show that $g=(a,c)$ is the universal $g$ such that $g...

@caveman it seems a little bit complicated
I think you should understand it before saying that
@pourjour, here is a different way math.stackexchange.com/a/342228/58512
if you imagine a,b,c written in prime factorization
b doesn't h ave any primes that a does
so (a,bc) = (a,c)
you just ignore b
since it doesn't share any primes with a
@caveman that's the problem becasue I'm trying to show that $d/bc ==> d/c$ using gauss theorem but I need (d,b)=1
what
23:45
to show this
so (a,bc) = (a,c)
we suppose that d1=(a,bc)
and d2 = (a,c)
(d,b) = 1 and d|bc implies d|c?
@caveman yes Gauss theorem am I wrong
?
what is Gauss theorem?
(Gauss proved many things)
3
@caveman Many? A gazillion things!
yeah :)
23:48
hhh yeah exactly the one which says a|bc and (a,b)=1 implies a/c
ok is there any lemma such (a,b)=d an d(a,c)=d implies (a,bc)=d
@pourjour,
> let $g\mid a$ and $g\mid bc$, we will show that $g|(a,c)$. By $(a,b)=1$ if $g\mid b$ then $g=1$, so suppose $g \not \mid b$, then $g \mid c$ and we are done.
if $a|bc$ and $(a,b)=1$ then we have some $k$ with $ak = bc$ and wish to prove there is some $h$ such that $ah = c$
since $ak=bc$ we can divide by $b$ to get $a(k/b)=c$ and $k/b$ is an integer
so take $h=k/b$
but a can't divise b and c at the same time this is an exception
just forget about it I'm confused today
do you have some ressources about the cramer manner
like the one used here
@pourjour, why do you care about this (a,bc) thing?
what did you study, that this came up in ?

« first day (965 days earlier)      last day (4353 days later) »